Endothelial dysfunction is associated with a greater depressive symptom score in a general elderly population: the Hoorn Study. Issue 7 (13th August 2013) - van Sloten, T. T.; Schram, M. T.; Adriaanse, M. C.; Dekker, J. M.; Nijpels, G.; Teerlink, T.; Scheffer, P. G.; Pouwer, F.; Schalkwijk, C. G.; Stehouwer, C. D. A.; Henry, R. M. A.
Abstract : Background: Endothelial dysfunction (ED), low-grade inflammation (LGI) and oxidative stress (OxS) may be involved in the pathobiology of depression. Previous studies on the association of these processes in depression have yielded contradictory results. We therefore investigated comprehensively, in a population-based cohort study, the association between ED, LGI and OxS on the one hand and depressive symptoms on the other. Method: We used data from the Hoorn Study and determined biomarkers of ED [flow-mediated dilatation (FMD), von Willebrand factor, soluble intercellular adhesion molecule 1 (sICAM-1), soluble vascular cell adhesion molecule 1, soluble thrombomodulin and soluble endothelial selectin], LGI [C-reactive protein, tumour necrosis factor- α, interleukin 6, interleukin 8, serum amyloid A, myeloperoxidase (MPO) and sICAM-1] and OxS (oxidized low density lipoprotein and MPO). Depressive symptoms were quantified by the Center for Epidemiologic Studies Depression Scale (CES-D) questionnaire ( n  = 493; age 68 years; 49.9% female). Regression analyses were performed with the use of biomarker Z scores. Adjustments were made for age, sex and glucose metabolism status (cohort stratification variables) and prior cardiovascular disease, hypertension, waist-to-hip ratio, cholesterol levels, education level, physical activity, dietary habits, and the use of antihypertensive and/or lipid-lowering medication and/or metformin (potential confounders). Results: After adjustment for age, sex and glucose metabolism status, one standard deviation increase in the ED Z score was associated with a 1.9 [95% confidence interval (CI) 0.7–3.1] higher CES-D score. Additional adjustments did not materially change this result. LGI and OxS were not associated with the CES-D score. Conclusions: ED, as quantified by an array of circulating biomarkers and FMD, was independently associated with depressive symptoms. This study supports the hypothesis that ED plays an important role in the pathobiology of depression.